PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA - Rahman, A. Faidlal (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2011)
Community empowerment is an important sector in developing tourist village. To develop tourist needs to use the resources of community, as community, as one of tourism stakeholders that has an important role to support an achievement of empowered to make them independence. Communirt empowerment activities, such as a). Meeting, b). Assistance, c). Financial aids, d). Infrastructure building, e). Tourism village organization formation, and f). Mutual assistance, done by the organizer really make community of Kembang Arum independence in developing tourism village. Keywords: Empowerment, Tourist Village and independence Cole, Stroma, Cultural Tourism Empowerment. In Melanie K. Smith and Mike Robinson, â€œCultural Tourism in a Changing World Polities Participation and (Re)Presentationâ€ British; Channel View Publication, 2006